Perilaku Dalam Pendidikan Islam - Abdus Salam; Achmad Taufiq; Mukhlasin; Muhammad Tis Asuh Shobirin; Titin Nurhidayati (AL-Ikhtiar : Jurnal Studi Islam, 2026)
Behavior in Islamic education is a fundamental aspect that lies at the core of the entire educational process. Islamic education is not solely oriented toward the transfer of religious knowledge, but rather emphasizes the formation of noble behavior and morals as a manifestation of faith and knowledge internalized within students. Behavior is understood as a primary indicator of the success of Islamic education, as it is through behavior that the values ​​of Islamic teachings are concretely realized in daily life. This study aims to analyze the concept of behavior in Islamic education and its urgency in developing individuals with faith, knowledge, and noble character. Islamic education views behavior as the result of an integration of cognitive, affective, and psychomotor aspects developed through learning processes, role models, habituation, and a valuable educational environment. Therefore, behavior is positioned not only as the end result of education but also as an integral part of the educational process itself. The study's findings indicate that effective Islamic education is one that is able to transform Islamic values ​​from the realm of texts into real-life contexts. Conscious, consistent, and responsible development of Islamic behavior contributes directly to the formation of individuals with integrity and to the realization of a just, harmonious, and civilized social order. Thus, placing behavior at the heart of Islamic education reaffirms the essence of Islamic education as a process of developing complete human beings (insān kāmil) who are not only intellectually intelligent but also morally just, and oriented toward the welfare of humanity and the sustainability of civilization.  Abstrak Perilaku dalam pendidikan Islam merupakan aspek fundamental yang menjadi inti dari seluruh proses pendidikan. Pendidikan Islam tidak hanya berorientasi pada transfer pengetahuan keagamaan, tetapi lebih menekankan pada pembentukan perilaku dan akhlak mulia sebagai manifestasi dari iman dan ilmu yang terinternalisasi dalam diri peserta didik. Perilaku dipahami sebagai indikator utama keberhasilan pendidikan Islam, karena melalui perilakulah nilai-nilai ajaran Islam terwujud secara nyata dalam kehidupan sehari-hari. Kajian ini bertujuan untuk menganalisis konsep perilaku dalam pendidikan Islam serta urgensinya dalam membentuk manusia yang beriman, berilmu, dan berakhlak mulia. Pendidikan Islam memandang perilaku sebagai hasil integrasi antara aspek kognitif, afektif, dan psikomotorik yang dibangun melalui proses pembelajaran, keteladanan, pembiasaan, dan lingkungan pendidikan yang bernilai. Oleh karena itu, perilaku tidak hanya diposisikan sebagai hasil akhir pendidikan, tetapi juga sebagai bagian integral dari proses pendidikan itu sendiri. Hasil kajian menunjukkan bahwa pendidikan Islam yang efektif adalah pendidikan yang mampu mentransformasikan nilai-nilai Islam dari ranah teks ke dalam konteks kehidupan nyata. Pembinaan perilaku islami secara sadar, konsisten, dan bertanggung jawab berkontribusi langsung pada pembentukan individu yang berintegritas serta pada terwujudnya tatanan sosial yang adil, harmonis, dan beradab. Dengan demikian, menempatkan perilaku sebagai jantung pendidikan Islam menegaskan kembali hakikat pendidikan Islam sebagai proses pembentukan manusia paripurna (insān kāmil) yang tidak hanya cerdas secara intelektual, tetapi juga bermoral, berkeadilan, dan berorientasi pada kemaslahatan umat manusia serta keberlanjutan peradaban